Jejaring radikalisme Islam di Indonesia : jejak sang pengantin bom bunuh diri - Singh, Bilveer, 1956-; Mulkhan, Abdul Munir, 1946- (Baciro, Yogyakarta : JB Publisher, 2011)
Islamic perspectives on radicalism and Islamic fundamentalism in Indonesia.
Includes bibliographical references (p. 147-152).
Keywords: Radicalism -- Religious aspects -- Islam; Islamic fundamentalism -- Indonesia; Islam -- Indonesia